2010
DOI: 10.1016/j.biomaterials.2010.06.031
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo performance of plasmonic nanobubbles as cell theranostic agents in zebrafish hosting prostate cancer xenografts

Abstract: Cell theranostics is a new approach that unites diagnosis, therapy and confirmation (guidance) of the results of therapy in one single process at cell level, thus principally improving both the rapidity and precision of treatment. The ideal theranostic agent will support all three of the above functions in vivo with cellular resolution, allowing individual assessment of disease state and the elimination of diseased cells while leaving healthy cells intact. We have developed and evaluated plasmonic nanobubbles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
144
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(146 citation statements)
references
References 54 publications
2
144
0
Order By: Relevance
“…Second, MCNPs serve as efficient photosensitizers with high absorption in the near-infrared region. [74][75][76][77] Therefore, they function as promising nanocarriers in photothermal and chemical combination therapy. Zhou et al 78 used these advantages to develop an effective dual-triggered (Hyal1/redox) chemophotothermal synergistic therapy nanomedicine, which presented efficient heat transformation for photothermal therapy.…”
mentioning
confidence: 99%
“…Second, MCNPs serve as efficient photosensitizers with high absorption in the near-infrared region. [74][75][76][77] Therefore, they function as promising nanocarriers in photothermal and chemical combination therapy. Zhou et al 78 used these advantages to develop an effective dual-triggered (Hyal1/redox) chemophotothermal synergistic therapy nanomedicine, which presented efficient heat transformation for photothermal therapy.…”
mentioning
confidence: 99%
“…Here, we analyze several experimental techniques for the imaging and quantitative analysis of transient vapor nanobubbles as single events and we troubleshoot some related errors. Due to the multiple biomedical applications of NBs and related phenomena, [34][35][36][37][38] it should be noted that we consider the transient events, but not the materials (particles) that are often also called nanobubbles. 39, 40 We also do not consider the cavitation of preexisting bubbles that is well studied elsewhere.…”
mentioning
confidence: 99%
“…A noninvasive amplification of the optical scattering amplitude with the PNB (relative to that of AuNP), selective mechanical and speedy damage to specific cells with bigger PNB, and optical guidance of therapy via the damage-specific signals of the bubbles were presented. A study conducted by Wagner et al 10 once again confirmed that PNB was capable of serving as an in vivo tunable theranostic cellular agent in zebrafish hosting prostate cancer xenografts.…”
Section: Gold-based Nanomaterialsmentioning
confidence: 85%